A Cross-sectional Study to Evaluate Causes of Maternal Mortality in Rural Areas of Punjab, India - Sarbhjit Kaur (JCDR Research and Publications Private Limited, 2021)
Introduction: Maternal mortality is an index of reproductive health of the society. In India illiteracy, late referrals, low socio-economic status of the community and direct causes are responsible for high incidence of maternal deaths which contributes to one-fifth of the global burden. Aim: To evaluate the causes of maternal death in rural areas of Punjab. Materials and Methods: The present retrospective cross-sectional study was conducted in 10 districts of Punjab, India chosen from five different zones i.e., east, west, north, south and central zone for a period of one year from 2016 to 2017. Information of all the deaths was taken from the civil surgeon office of the chosen district and then data of maternal deaths occurring within 42 days of delivery was collected by visiting patient’s residence and verbal autopsy was conducted. The data was collected and entered in predesigned proforma and percentages were calculated in Microsoft Excel version 2016. Results: A total of 67 maternal deaths were noted from above five zones, out of total rural population of 94,59,553. Maximum (n=51) maternal deaths were between age range of 20-30 years. Of these 67, majority 29 (43.28%) were illiterate, 66 (98.5%) women belonged to middle and low socio-economic status, 55 (82.1%) deaths occurred in the postnatal period, 33 (49.25%) occurred at more than 37 weeks period of gestation and 51 (76.12%) were due to direct causes. Out of 67 deaths, haemorrhage (n=29) was the most common cause. Anaemia contributed to 16.7% (11) as an indirect cause of maternal death. Conclusion: The maximum maternal deaths were contributed by illiterate women from middle and low socio-economic status. The most common cause was postpartum haemorrhage followed by pre-eclampsia/eclampsia.